Psychosocial work factors and their predictive impact on the health and well-being of informal caregivers: A study with the Copenhagen Psychosocial Questionnaire - Romão, Â.; Correia, I. (Community, Work and Family)
Caring for a dependent person poses significant challenges to the psychological and physical health of informal caregivers. Although extensive research has examined a wide range of individual and sociodemographic factors associated with informal caregivers’ health and well-being, the impact of psychosocial factors within caregiving work remains underexplored. This study assesses the psychosocial factors inherent to informal caregiving work environment and analyzes their unique impact on informal caregivers’ health and well-being during the COVID-19 pandemic. A cross-sectional study was conducted with 178 Portuguese informal caregivers (Mage = 52.79; SD = 11.19) who completed the Portuguese medium version of the Copenhagen Psychosocial Questionnaire II (COPSOQ II). Furthermore, we controlled for the potential impact of individual and sociodemographic factors. The results showed that informal caregivers report high demands (cognitive and emotional) and low resources (recognition, support, quality of leadership, and justice and respect) in the context of caregiving work. Hierarchical regression analysis showed that, when considered together, only work demands negatively impacted caregivers’ health and well-being, while predictability, role clarity, and a trustworthy relationship with the Portuguese State had a positive impact. These findings highlight the need for interventions focusing on the above-mentioned factors to promote the health and well-being of informal caregivers.